Algorithmic problem solving - Backhouse, Roland C. , 1948- (Wiley, 2011)
Novel approach to the mathematics of problem solving, in particular how to do logical calculations. Many of the problems are well-known from (mathematical) puzzle books. The solution method in the book is new and more relevant to the true nature of problem solving in the modern IT-dominated world